Experimental investigation on the evolution of bubble behavior in subcooled flow boiling in narrow rectangular channel based on bubble tracking algorithm - Lv, Kezhong; Zhou, Linglan; Chen, Yong; Gao, Hong (Frontiers in Energy Research, 2023)
The nucleate subcooled boiling is an efficient heat transfer form and plays an important role in many cooling applications. The size and distribution of bubbles in subcooled boiling have considerable influence on boiling heat transfer. In this paper, subcooled flow boiling experiment is carried out to investigate t the nucleation point density and detachment frequency of bubbles under different system pressure, and the test section is full transparent. The experimental cross-section was fully transparent. Since the whole body of the test section is composed of transparent materials, it can be observed from different directions to obtain high quality images. A bubble tracking algorithm has been developed, which can effectively determine the diameter and position of detached bubbles, thereby inferring the nucleation point density and detachment frequency of bubbles. Besides, the distinctive properties of bubble nucleation within narrow rectangular channel are verified by comparing bubble detachment diameters with existed models. Finally, models for bubble nucleation point and detachment frequency under different operating conditions were proposed and verified through experimental results.